Evaluating the MEDAN score: An alternative diagnostic instrument to acute myocardial infarction for resource-limited settings - Napitupulu, Friendina; Lubis, Anggia Chairuddin; Teuku Bob Haykal; Lubis, Hilfan Ade Putra; Kamal Kharrazi Ilyas; Harris Hasan (Universitas Brawijaya, 2026)
Background: Acute Myocardial Infarction (AMI) is one of the leading cause of death worldwide. Limited access to biomarker testing, especially troponin, poses a significant challenge for rapid and accurate diagnosis, particularly in resource-limited settings. We previously proposed Myocardial infarction Early DiAgnosis instrumeNt (MEDAN) score as a tool for predicting AMI. Objective: To conduct internal validation and assess the reproducibility of the MEDAN score in distinct patient cohorts. Methods: This study was conducted at Adam Malik Hospital in Medan, Sumatera Utara. A research form was used to gather data from electronic medical records. Data were collected retrospectively from January to December 2024 and prospectively since January 2025. Chi-square tests were applied to determine sensitivity values, specificities, negative predictive value (NPV), and positive predictive value (PPV). ROC analysis was used to compare MEDAN score to the HEART and GRACE scores. Result: This study included 685 patients: 417 with AMI and 268 without AMI. Patients with AMI had higher heart rate as well as HEART, GRACE, and MEDAN scores, but lower systolic blood pressure. The MEDAN score demonstrated a sensitivity of 78.2%, specificity of 60.7%, PPV of 71.2%, and NPV of 69%. The MEDAN score showed good diagnostic ability, outperforming the HEAR score and GRACE score without troponin point, but remained less effective than HEART and GRACE scores when troponin was included. Conclusion: The MEDAN score demonstrates good diagnostic ability for detecting AMI and may serve as practical alternative in healthcare facilities with limited access to biomarker testing.